Ascomicetes of the Cozumel Island Biosphere Reserve, Mexico - Raymundo, Tania; Martínez-Pineda, Michelle; Reyes, Pamela E.; Cobos-Villagrán, Aurora; García- Martínez, Yenitze A.; Tun, Adrián A.; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2021)
Background and Aims: Ascomycetes are the most diverse group of the kingdom Fungi; they have been described as saprobes, necrotrophs, biotrophs and endophytes. On the Island Cozumel, Quintana Roo, Mexico, 29 species have recently been cited; however, there is no exclusive study of this group. The objective of this study is to present a list of ascomycetes species from three Protected Natural Areas in the Cozumel Island Biosphere Reserve, Mexico.Methods: Four explorations were carried out in the Natural Protected Areas of the Cozumel Island Biosphere Reserve: Centro de Conservación y Educación Ambiental, Parque Ecológico Punta Sur and Zona Arqueológica de San Gervasio, Chen-tuk; all are administrated by the Fundación Parques y Museos of Cozumel. The collected specimens were studied, described and determined according to the traditional mycological techniques. The material is deposited in the ENCB Herbarium.Key results: Forty species of ascomycetes are determinated, of these 15 are cited for the first time for Quintana Roo, and eight are recorded for Cozumel Island. Bertia tropicalis is a new record from Mexico and Platystomum mexicanum is described as a species new to science.Conclusions: The class Sordariomycetes is the best represented with 28 species, while the order Xylariales with 25 species has 62.5% of the total of 40 registered. The family Hypoxylaceae, with 40% of the determinated taxa, is the best represented family. Hypoxylon lenormandii, Rhytidhysteron neorufulum and R. rufulum were found in all Natural Protected Areas studied.